Collaborative Study of the NCCLS and Flow Cytometry Methods for Antifungal Susceptibility Testing of Candida albicans - Chaturvedi, Vishnu (American Society for Microbiology, 2004)
One hundred clinical isolates of Candida albicans were tested for amphotericin B and fluconazole susceptibilities by the National Committee for Clinical Laboratory Standards (NCCLS) broth microdilution test at center 1 (C1). The same isolates were tested blinded at center 2 (C2) by NCCLS and flow cytometry (FC) methods. The agreement between NCCLS and FC methods ranged from 96 to 99%.